Data Mining as a Guide for the Construction of Crosslinked Nanoparticles with Low Immunotoxicity via Controlling Polymer Chemistry and Supramolecular Assembly - Elsabahy, Mahmoud (Acc Chem Res, 2015)
[Image: see text] The potential immunotoxicity of nanoparticles that are currently being approved or in different phases of clinical trials or under rigorous in vitro and in vivo characterizations in several laboratories has recently raised special attention. Products with no apparent in vitro or in vivo toxicity may still trigger the various components of the immune system, unintentionally, and lead to serious adverse reactions. Cytokines are one of the useful biomarkers to predict the effect of biotherapeutics on modulating the immune system and for screening the immunotoxicity of nanoparticles, both in vitro and in vivo, and were found recently to partially predict the in vivo pharmacokinetics and biodistribution of nanomaterials. Control of polymer chemistry and supramolecular assembly provides a great opportunity for construction of biocompatible nanoparticles for biomedical clinical applications. However, the sources of data collected regarding immunotoxicities of nanomaterials are diverse and experiments are usually conducted using different assays and under specific conditions, making direct comparisons nearly impossible and, thus, tailoring properties of nanomaterials based on the available data is challenging. In this account, the effects of chemical structure, crosslinking, degradability, morphology, concentration and surface chemistry on the immunotoxicity of an expansive array of polymeric nanomaterials will be highlighted, with focus being given on assays conducted using the same in vitro and in vivo models and experimental conditions. Furthermore, numerical descriptive values have been utilized, uniquely, to stand for induction of cytokines by nanoparticles. This treatment of available data provides a simple and easy way to compare the immunotoxicity of various nanomaterials, and the values were found to correlate-well with published data. Based on the investigated polymeric systems in this study, valuable information has been collected that aids in the future design of nanomaterials for biomedical applications, which include: a) Immunotoxicity of nanomaterials is concentration- and dose-dependent; b) Synthesis of degradable nanoparticles is essential to decrease toxicity; c) Crosslinking minimizes the release of free polymeric chains and maintains high stability of nanoparticles, thereby, lowering their immunotoxicity; d) Lowering amine density for cationic polymers that are being utilized for nucleic acids delivery lowers the toxicity of nanoparticles; e) Among neutral, zwitterionic, anionic and cationic nanomaterials, neutral and cationic nanoparticles usually have the lowest and highest immunotoxicity, respectively; f) Morphology, dimension and surface chemistry have a great influence on the ability of nanomaterials to interact with the various components of the biological system and to modulate the immune system.